1998
DOI: 10.1080/02841859809172229
|View full text |Cite
|
Sign up to set email alerts
|

Gadopentetate dimeglumine as a contrast agent in peripheral angioplasty

Abstract: Gadopentetate dimeglumine (Gd-DTPA) is widely used as a contrast agent in MR imaging. We report on a case in which Gd-DTPA was used as the contrast agent during angioplasty in a patient who had recently had an adverse reaction to a non-ionic iodinated contrast medium. Gd-DTPA allowed a diagnostic angiogram to be performed with no side effects, and may thus be a useful contrast agent at angioplasty in patients with contra-indications to iodinated contrast media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…4,5 In addition, several cases of intra-arterial gadolinium application for different angiographic visualizations, such as the aorta, lower extremities, and renal, cerebral, and carotid arteries, have been described. [6][7][8][9] Furthermore, gadolinium has even successfully been used for coronary angiography. [10][11][12][13][14] For a long period of time, there was a lack of information with regard to the intra-arterial application of gadolinium during angiography in patients with chronic renal insufficiency, especially concerning the dosage, which is higher as in magnetic resonance angiography.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 In addition, several cases of intra-arterial gadolinium application for different angiographic visualizations, such as the aorta, lower extremities, and renal, cerebral, and carotid arteries, have been described. [6][7][8][9] Furthermore, gadolinium has even successfully been used for coronary angiography. [10][11][12][13][14] For a long period of time, there was a lack of information with regard to the intra-arterial application of gadolinium during angiography in patients with chronic renal insufficiency, especially concerning the dosage, which is higher as in magnetic resonance angiography.…”
Section: Introductionmentioning
confidence: 99%
“…Gadolinium is a nonionic contrast medium with an osmolality of 789 mOsm/kg, and is currently approved for intravenous use in magnetic resonance imaging (MRI) (Omniscan Package Insert, Amersham Health, Princeton, NJ) 4,5 . In addition, several cases of intra‐arterial gadolinium application for different angiographic visualizations, such as the aorta, lower extremities, and renal, cerebral, and carotid arteries, have been described 6–9 . Furthermore, gadolinium has even successfully been used for coronary angiography 10–14 .…”
Section: Introductionmentioning
confidence: 99%
“…Little experience with gadodiamide-guided peripheral and renal angioplasties has been reported. 11,12,17 However, we chose to use gadodiamide because of fewer reported side effects compared with gadolinium-based agents. Murphy et al 28 retrospectively analyzed 74275 gadodiamide injections and found 0.015% nonallergic and 0.016% mild allergy-like reactions, but no moderate or severe sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 There is limited clinical experience with gadolinium or gadodiamide in J ENDOVASC THER 2002;9:625-632 ࡗ ࡗ intra-arterial angiography or computed tomography. [9][10][11][12][13][14][15][16][17] The use of gadodiamide in peripheral and renal artery interventions has not been studied extensively, 11,12,17 so we explored the feasibility of gadodiamide as a contrast agent in DSA/angioplasty and its impact on renal and thyroid function.…”
mentioning
confidence: 99%
“…As a result, other techniques have been explored to allow angiographic intervention without using standard radiographic contrast agents. Both carbon dioxide 9,10 and gadolinium 11 have been used successfully, but these methods may be time consuming and expensive. On the other hand, ultrasound has been widely accepted as an alternative guidance tool, [3][4][5][6] which avoids the use of ionizing radiation and radiographic contrast inherent to fluoroscopy.…”
Section: Discussionmentioning
confidence: 99%